Rethinking law, regulation, and technology - Brownsword, Roger (Rethinking law., 2022)
This insightful book presents a radical rethinking of the relationship between law, regulation, and technology. While in traditional legal thinking technology is neither of particular interest nor concern, this book treats modern technologies as doubly significant, both as major targets for regulation and as potential tools to be used for legal and regulatory purposes. It explores whether our institutions for engaging with new technologies are fit for purpose. Having depicted a legal landscape that includes legal rules and principles, regulatory frameworks, technical measures and technological governance, this thought-provoking book presents further exercises in rethinking. These exercises confront communities with a fundamental question about how they are to be governed-by humans using rules or by technical measures and technological management? Chapters rethink the traditional arguments relating to legality, the rule of law, legitimacy, regulatory practice, dispute resolution, crime and control, and authority and respect for law. Examining the role of lawyers and law schools in an age of governance by smart technologies, Rethinking Law, Regulation, and Technology will be a key resource for students and scholars of law and technology, digital innovation and regulation and the law"--